Flower-like nickel-cobalt hydroxides converted from phosphites for high rate performance hybrid supercapacitor electrode materials. (20th August 2016) - Gou, Jianxia; Xie, Shengli; Liu, Yanru; Liu, Chenguang
Graphical abstract: The electrochemical performance of Ni−Co hydroxides converted from phosphites can be enhanced by adjusting material structure and valence state of Cobalt. Highlights: Flower-like Ni-Co hydroxide is fabricated through chemically treating of phosphite. Chemical treatment induces the evolution of morphology and emergence of CoOOH. The Ni-Co hydroxide electrode shows high rate performance and specific capacitance. High performance is due to dual-channel structure and appropriate amount of Co 3+ . Abstract: Ni-Co hydroxides have been extensively studied as electrode materials for hybrid supercapacitors. In this work, we report an effective method to significantly improve the rate performance of Ni-Co hydroxides through engineering the dual-channel structure and tuning the valence state of Cobalt, which is realized through a facile in suit chemical treatment of phosphites. The specific capacitance of the obtained flower-like Ni-Co hydroxide electrode is 1425 F g −1 at 20 A g −1, which is 83.9% of 1698 F g −1 at 1 A g −1 . Simultaneously, a moderate cycling stability with an efficiency of 80.6% after cycling 4000 times at a current density of 10 A g −1 is obtained. Moreover, an energy density of 40.1 Wh kg −1 at a power density of 801.2 W kg −1 has been achieved in an assembled aqueous asymmetric supercapacitor, using Ni-Co hydroxide as positive electrode material and activated carbon as negative electrode material. Our study shows that the chemical treatment evokes morphology and phase transformation and induces partial Co 2+ conversion to a more conductive Co 3+ state. And the electrochemical performance has a significant relationship with the microstructure and valence state of Cobalt.